THE DEVELOPMENT OF THE TOURISM INDUSTRY - Malem Munthe, Juliany Serta (Jurnal Ilmiah Administrasi Publik, 2013)
Abstract: The Development of The Tourism Industry. This study is designed to describe and analyze the development of tourism industry in Karo Regency, Indonesia. Karo Regency is rich in natural and cultural resources of tourism, but local government is unable to maximize it. There are several obstacles make the development of tourism industry is not meeting the expectation. The research method used in this study is the qualitative method. For data collection, the researcher conducted field work, used multiple sources of evidence and Â interviews with relevant subjects either officials of Department of Culture and Tourism or other department involved. Some recommendations are providing such as: the development of tourismÂ  in Karo Regency must be supported by other types of tourism; department of culture and tourism should be able to enhance the relationships with other relevant departments to create policies, programs, and projects which attract the interest of private sector and society,Â  improve the competency of human resources and the focus of tourism should be in infrastructure and facilities. It is required financial support from government to sponsor tourism, especially for promotional activities, maintaining tourismâs objectives and development. Â  Key words: tourism, development, policy Â  Abstrak: Pengembangan Industri Pariwisata. Penelitian ini dirancang untuk mendeskripsikan dan menganalisis perkembangan industri pariwisata di Kabupaten Karo, Indonesia. Kabupaten Karo kaya akan sumber daya alam dan budaya pariwisata, tetapi pemerintah daerah tidak dapat memaksimalkan itu. Ada beberapa kendala membuat pengembangan industry pariwisata tidak memenuhi harapan. Metode penelitian yang digunakan dalam penelitian ini adalah metode kualitatif. Untuk pengumpulan data, peneliti melakukan kerja lapangan, digunakan beberapa sumber bukti dan wawancara dengan mata pelajaran yang relevan baik pejabat Departemen Kebudayaan dan Pariwisata atau rekomendasi lain departemen yang terlibat. Beberapa menyediakan seperti: pengembangan pariwisata di Kabupaten Karo harus didukung oleh jenis pariwisata; departemen kebudayaan dan pariwisata harus mampu meningkatkan hubungan dengan departemen terkait lainnya untuk membuat kebijakan, program, dan proyek-proyek yang menarik minat sektor swasta dan masyarakat, meningkatkan kompetensi sumber daya manusia dan fokus pariwisata harus dalam sarana dan prasarana. Hal ini diperlukan dukungan dana dari pemerintah untuk mensponsori pariwisata, terutama untuk kegiatan promosi, mempertahankan tujuan dan pengembangan pariwisata itu. Â  Kata kunci: pariwisata, pembangunan, kebijakan